CEDRA: A Tool to Help Consumers Assess Risk for Ear Disease. Issue 6 (November 2019) - Klyn, Niall A. M.; Kleindienst Robler, Samantha; Bogle, Jamie; Alfakir, Razan; Nielsen, Donald W.; Griffith, James W.; Carlson, Deborah L.; Lundy, Larry; Dhar, Sumitrajit; Zapala, David A.
Abstract : This article introduces the Consumer Ear Disease Risk Assessment (CEDRA) tool. CEDRA is a brief questionnaire designed to screen for targeted ear diseases. It offers an opportunity for consumers to self-screen for disease before seeking a hearing device and may be used by clinicians to help their patients decide the appropriate path to follow in hearing healthcare. Here we provide highlights of previously published validation in the context of a more thorough description of CEDRA's development and implementation. CEDRA's sensitivity and specificity, using a cut-off score of 4 or higher, was 90% and 72%, respectively, relative to neurotologist diagnoses in the initial training sample used to create the scoring algorithm (n = 246). On a smaller independent test sample (n = 61), CEDRA's sensitivity and specificity were 76% and 80%, respectively. CEDRA has readability levels similar to many other patient-oriented questionnaires in hearing healthcare, and informal reports from pilot CEDRA-providers indicate that the majority of patients can complete it in less than 10 min. As the hearing healthcare landscape changes and provider intercession is no longer mandated, CEDRA provides a measure of safety without creating a barrier to access. Abstract : Supplemental Digital Content is available in the text.